2016
DOI: 10.1002/2015je004905
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and relative timing of large lakes in Gale crater (Mars) after the formation of Mount Sharp

Abstract: The quantification of lake levels in Gale crater is important to define the hydrologic and climatic history experienced by the sedimentary deposits found by Curiosity. We propose that there were at least three major lake stands within Gale, each persisted >1000 years, and all occurred after Mount Sharp reached close to its current topographic form. Deltaic deposits off the southern rim of Gale, derived from incision of Farah Vallis, and corresponding deposits off the southern flank of Mount Sharp define the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
148
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(158 citation statements)
references
References 71 publications
9
148
1
Order By: Relevance
“…A transition to sustained arid conditions is then required to explain the evaporitic sulfate cementation of aeolian sediments found at higher elevations in the mound [Milliken et al, 2010;Thomson et al, 2011], similar to the sulfate deposits found by the Mars Exploration Rover Opportunity at Meridiani Planum [Grotzinger et al, 2005;McLennan et al, 2005;Squyres and Knoll, 2005;Arvidson et al, 2006Arvidson et al, , 2014 and elsewhere on Mars [Bibring et al, 2006;Glotch and Rogers, 2007;Murchie et al, 2009;Zabrusky et al, 2012]. Thus, although evidence supports increasingly arid conditions on Mars during the transition from the Noachian through Hesperian, the climate was clearly variable on shorter timescales with returns to Noachian-like conditions for sufficiently long periods of time to produce the observed deltas and associated late-stage lakes [Palucis et al, 2016]. Finally, the results of this work indicate a return to semiarid conditions at some point during the Hesperian or later in order to produce the late-stage Gale crater lakes.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…A transition to sustained arid conditions is then required to explain the evaporitic sulfate cementation of aeolian sediments found at higher elevations in the mound [Milliken et al, 2010;Thomson et al, 2011], similar to the sulfate deposits found by the Mars Exploration Rover Opportunity at Meridiani Planum [Grotzinger et al, 2005;McLennan et al, 2005;Squyres and Knoll, 2005;Arvidson et al, 2006Arvidson et al, , 2014 and elsewhere on Mars [Bibring et al, 2006;Glotch and Rogers, 2007;Murchie et al, 2009;Zabrusky et al, 2012]. Thus, although evidence supports increasingly arid conditions on Mars during the transition from the Noachian through Hesperian, the climate was clearly variable on shorter timescales with returns to Noachian-like conditions for sufficiently long periods of time to produce the observed deltas and associated late-stage lakes [Palucis et al, 2016]. Finally, the results of this work indicate a return to semiarid conditions at some point during the Hesperian or later in order to produce the late-stage Gale crater lakes.…”
Section: Discussionsupporting
confidence: 66%
“…Decreasing the annual precipitation for a given aridity index (and thus decreasing the evaporation potential proportionally) results in a proportional decrease in aquifer recharge. The horizontal dashed lines are the lake stands inferred by Palucis et al [2016] and correspond to the colored contours in Figure 1, while the vertical lines delineate climate zones. In other words, at lower precipitation rates Gale captures more of the regional groundwater flow and the Gale lakes are stable at higher aridity indices.…”
Section: 1002/2017gl074654mentioning
confidence: 99%
See 2 more Smart Citations
“…These features are likely to have resulted from a process of groundwater upwelling followed by water table fluctuations and eventual groundwater recession. The presence of a large number of water‐formed features in all these deep basins (Figure ) is a compelling sign that Mars once had large amounts of water stored as groundwater that debouched into the intercepting craters to form lacustrine systems (Palucis et al, ). The purpose of this work is to identify these water‐related features at a basin level, define their depositional environments and then analyze them holistically at a planetary scale to identify whether they are the result of a single planet‐wide control (Figure ).…”
Section: Introductionmentioning
confidence: 99%